Listeria monocytogenes, a silent foodborne pathogen in Ecuador - Mejía, Lorena; Espinosa-Mata, Estefanía; Freire, Ana Lucía; Zapata, Sonia; González-Candelas, Fernando (Frontiers in Microbiology, 2023)
Listeria monocytogenes is a foodborne pathogen that can produce serious, even fatal, infections. Among other foods, it can be found in unpasteurized dairy and ready-to-eat products. Surveillance of L. monocytogenes is of great interest since sources of infection are difficult to determine due to the long incubation period, and because the symptoms of listeriosis are similar to other diseases. We performed a genomic study of L. monocytogenes isolated from fresh cheeses and clinical samples from Ecuador. Sixty-five isolates were evaluated and sequenced, 14 isolates from cheese samples and 20 from clinical listeriosis cases from the National Institute of National Institute of Public Health Research, and 31 isolates from artisanal cheese samples from 8 provinces. All isolates exhibited heterogeneous patterns of presence of pathogenicity islands. All isolates exhibited at least 4 genes from LIPI-1, but all references (26 L. monocytogenes closed genomes available in NCBI database) showed the complete island, which encompasses 5 genes, but is present in only two Ecuadorian isolates. Most isolates lacked gene actA. Genes from LIPI-2 were absent in all isolates. LIPI-3 and LIPI-4 werepresent only in a few references and isolates. With respect to the stress survival islets, our samples either presented SSI-1 or SSI-F2365, except for one isolate that presented SSI-F2365 and also one gene from SSI-1. None of the samples presented SSI-2. The predominant ST (sequence type) was ST2 (84.62% 55/65), and the only ST found in food (93.33% 42/45) and clinical samples (65% 13/20). Isolates did not group according to their sampling origin, date or place in a phylogenetic tree obtained from the core alignment. The presence of ST2 in food and clinical samples, with high genomic similarity, suggests a foodborne infection risk linked to the consumption of fresh cheeses in Ecuador.